Influence of extraction process (pre-treatment time) on the characteristic of black tilapia fish skins gelatin - Ismail, Norhasikin; Abdullah, Hasan Zuhudi (Trans Tech Publications, Switzerland, 2017)
Gelatin from black tilapia fish skins is perhaps one of the popular alternative source of gelatin, to be used various food and pharmaceutical applications. The extraction process of gelatin from black tilapia skin was carried out via acid treatment, using 0.03 M of hydrochloric acid (HCl) with different pre-treatment times (4 h, 16 h and 24 h) and followed by a final extraction with water at different temperature of 45 °C and 65 °C. This study explores the effects of pre-treatment time to the yield and moisture content of gelatin. The highest yield have been recorded 22.48 % and 21.5 % while moisture content were 5.63% and 44.25% for both extracted temperatures (45°C and 65°C) respectively that treated for 4 h of pre-treatment times. Fourier transform infrared spectroscopy (FTIR) has been used to analyse the interactions and characteristics between functional groups of the gelatin